Monitoring of steam chamber in steam-assisted gravity drainage based on the temperature sensitivity of oil sand - Yunfeng GAO; Ting'en FAN; Jinghuai GAO; Hui LI; Hongchao DONG; Shigang MA; Qingfeng YUE (Petroleum Exploration and Development, 2021)
Thermosensitivity experiments and simulation calculations were conducted on typical oil sand core samples from Kinosis, Canada to predict the steam chamber development with time-lapse seismic data during the steam-assisted gravity drainage (SAGD). Using an ultrasonic base made of polyether ether ketone resin instead of titanium alloy can improve the signal energy and signal-to-noise ratio and get clear first arrival; with the rise of temperature, heavy oil changes from glass state (at –34.4 °C), to quasi-solid state, and to liquid state (at 49.0 °C) gradually; the quasi-solid heavy oil has significant frequency dispersion. For the sand sample with high oil saturation, its elastic property depends mainly on the nature of the heavy oil, while for the sand sample with low oil saturation, the elastic property depends on the stiffness of the rock matrix. The elastic property of the oil sand is sensitive to temperature noticeably, when the temperature increases from 10 °C to 175 °C, the oil sand samples decrease in compressional and shear wave velocities significantly. Based on the experimental data, the quantitative relationship between the compressional wave impedance of the oil sand and temperature was worked out, and the temperature variation of the steam chamber in the study area was predicted by time-lapse seismic inversion.